KEANEKARAGAMAN SPESIES ULAR DI DESA PERING, KECAMATAN BLAHBATUH, KABUPATEN GIANYAR, BALI - ARIUS HADY BUDIADA, I GEDE MADE (Jurnal Biologi Udayana; Vol 21 No 1 (2017): JURNAL BIOLOGI UDAYANA, 2017)
Snakes are cold-blooded reptiles belong to the Order Squamata, Suborder Serpentes. Snakes often found in lowlands, highlands, trees, soil, water and swamps. People in the Pering village especially in Banjar Perang Sada have less knowledge about venomous and non-venomous snakes. Therefore, it is important to investigate the diversity of snakes in the Pering village, Blahbatuh, Gianyar. This study was conducted on 28 January – 4 February 2015. Data collection was performed by direct observation along the potential snake habitats in two plots rice field near residential area and near the Pura Beji. Data collection was performed during night time from at 7:00 to 11:00 PM with sampling focused on Banjar Perang Sada. Individual snake found was cought and identified in situ. This research found 9 species of snakes namely, Ahaetulla prasina, Boiga cynodon, Dendrelaphis pictus, Pareas carinatus, Ptyas korros, Rhabdophis chrysargos, Xenochrophis piscator, Bungarus fasciatus, and Trimeresurus insularis, the most commonly found was Dendrelaphis pictus.